The dark side of nation states : ethnic cleansing in modern Europe - Ther, Philipp (War and genocide, 2014)
Why was there such a far-reaching consensus concerning the utopian goal of national homogeneity in the first half of the twentieth century? Ethnic cleansing is analyzed here as a result of the formation of democratic nation-states, the international order based on them, and European modernity in general. Almost all mass-scale population removals were rationally and precisely organized and carried out in cold blood, with revenge, hatred and other strong emotions playing only a minor role. This book not only considers the majority of population removals which occurred in Eastern Europe, but is also an encompassing, comparative study including Western Europe, interrogating the motivations of Western statesmen and their involvement in large-scale population removals. It also reaches beyond the European continent and considers the reverberations of colonial rule and ethnic cleansing in the former British colonies.--